Enhancing Cancer Registry Data for Comparative Research at the Nairobi Hospital - Ondego, Elvis M.; Ochieng, Lucy A. (European Journal of Applied Sciences, 2024)
The global incidence of cancer is rising, with GLOBOCAN projecting over 1.27 million new cases and one million deaths by 2030. This trend underscores the need for robust cancer registries to inform policy, healthcare financing, and resource allocation. High-quality cancer registry data is essential for comparative effectiveness research, which evaluates the efficacy of different treatments and interventions. This study aimed to determine the prevalence and distribution of various cancer types by age and gender among patients at The Nairobi Hospital (TNH). A retrospective cohort review of 362 patient records from TNH was conducted. Data were collected from confirmed cancer cases using ICDO and IARC guidelines and analyzed using CANREG-5 and Excel 2016. Among the 362 cases, 34% were male and 66% were female. Cervical cancer was most prevalent (30%), followed by prostate and breast cancers (13% each). Age-specific data showed the highest cancer prevalence in males aged 60-75 and females aged 45-59. Childhood cancers were less than 2%. The study highlights the importance of enhancing cancer registry data for effective cancer care and policy-making.